THE ROLE OF SOCIAL MEDIA ON THE STUDENT'S ENGLISH LEARNING ACHIEVEMENT - Ade Noviyanti; Franscy (Dialectical Literature and Educational Journal, 2021)
This research focuses on the analysis of using Google Classroom, Zoom and YouTube as social media applications to learning English. The objective of this research is to know the role of social media (Zoom, Google Classroom and YouTube) for the student’s learning achievement at SMA Islam As-Syafi’iyah 01. This research used the descriptive analysis method. The data of this research are questions given to the students using google form and collecting their final score from the English teacher. Then, the result of this research; Most of students (57 % of 100 samples) using their gadgets more than three hours per day. The observation found 96% of 100 population and from questionnaire got 70% are always and 19% are usually using social media for learning. 79,7% of students said that Google Classroom, Zoom and YouTube are popular and easy to use in language learning. Based on the questionnaire researchers found 53% are always and 30% are usually agreed when they must study using Google Classroom, Zoom and YouTube. Researchers found that 18% of the population are always and the other 48% are usually got good final scores during online learning using social media. More ever using social media, make students have appropriate platform to study in pandemic era and also can improve their achievement using social media at once.